Changes in Plasma Ghrelin and Serum Leptin Levels after Cisplatin-Based Transcatheter Arterial Infusion Chemotherapy for Hepatocellular Carcinoma. (7th March 2013) - Matsumura, Tomoaki; Arai, Makoto; Yoshikawa, Masaharu; Sudo, Kentaro; Nakamura, Kazuyoshi; Katsuno, Tatsuro; Kanai, Fumihiko; Yamaguchi, Taketo; Yokosuka, Osamu
Abstract : Background and Objective. Cisplatin-based chemotherapy is widely recognized to cause severe gastrointestinal disorders like nausea, vomiting, and appetite loss. The aim of this study was to assess whether cisplatin-based transcatheter arterial infusion (TAI) chemotherapy reduces plasma ghrelin levels and food intake in hepatocellular carcinoma (HCC) patients. Methods. Seventeen patients with HCC who underwent cisplatin-based TAI chemotherapy (80–100 mg/body) were enrolled in this study. Changes in peptide hormones, including ghrelin and leptin, as well as cytokines, were measured before and after chemotherapy. Appetite was evaluated by visual analog scale (VAS) and food intake was scored by eleven stages (0–10). Results. Appetite and food intake were significantly decreased after chemotherapy (P < 0.05 ). Plasma acylated ghrelin levels before therapy and at day 1, day 7, and day 14 after chemotherapy were 10.4 ± 7.2, 4.7 ± 4.7, 11.7 ± 8.9, and 9.3 ± 6.6 fmol/mL, respectively. The level on day 1 was decreased significantly (P < 0.05 ). In contrast, the levels of leptin, granulocyte colony-stimulating factor (G-CSF), and monocyte chemotactic protein-1 (MCP-1) on day 1 were increased significantly (P < 0.05 ). Conclusions. TAI for HCC reduced plasma acylated ghrelin levels, appetite, and food intake significantly. In addition, it increased serum leptin levels.